Translators of the regime: the profession during the Salazar dictatorship in Portugal - Chumbo, Isabel (2005)
In a time when translators are fighting for their rights it is also necessary to evaluate what happened in the past. This paper examines the policy towards translation during the dictatorship in Portugal, especially under the presidency of Salazar. The regime's promotion of certain translations selected on criteria that draw on notions of cultural specificity is thoroughly analyzed. On one hand the translators directly employed by the regime had to work within the boundaries of censorship and therefore acceptability, on the other hand collections of translated literature flourished in Portugal for several years, achieving popularity. It seems important to examine why that happened, especially why the regime ignored (if it did) those translations and why it worked so hard on other kind of translations to promote Portugal and state suspicion towards everything that was foreign. This contradiction combined with the state of the art in those days may contribute to the understanding both of an under-researched area of translation studies in Salazar's Portugal and of the ideological context of translation.